2005
DOI: 10.1183/09031936.05.00067104
|View full text |Cite
|
Sign up to set email alerts
|

QT interval dispersion in obstructive sleep apnoea syndrome patients without hypertension

Abstract: QT interval dispersion (QTd) reflects inhomogeneity of repolarisation. Delayed cardiac repolarisation leading to the prolongation of the QT interval is a well-characterised precursor of arrhythmias. Obstructive sleep apnoea syndrome (OSAS) can cause cardiovascular complications, such as arrhythmias, myocardial infarction, and systemic and pulmonary hypertension. The aim of this study was to assess QTd in OSAS patients without hypertension.A total of 49 subjects without hypertension, diabetes mellitus, any card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
0
21
1
2
Order By: Relevance
“…7 In contrast to the present investigation, they showed that corrected QTd is increased in patients with severe OSA. The high value of AHI (42.4 ± 17.6/ h) can be the reason for the difference between the 2 studies (we assessed only 25.83 ± 18.5/ h AHI).…”
Section: Discussioncontrasting
confidence: 53%
“…7 In contrast to the present investigation, they showed that corrected QTd is increased in patients with severe OSA. The high value of AHI (42.4 ± 17.6/ h) can be the reason for the difference between the 2 studies (we assessed only 25.83 ± 18.5/ h AHI).…”
Section: Discussioncontrasting
confidence: 53%
“…It has also been implicated as an independent risk factor for cardiovascular diseases such as myocardial infarction, hypertension, heart failure, arrhythmias, and stroke [6][7][8][9][10][11]. We showed that, especially in females with metabolic syndrome risk, evaluation of metabolic syndrome criteria may play an important role in predicting OSA severity with high sensitivity (86.6%) and high negative predictivity (85.7%) [12].…”
Section: Introductionmentioning
confidence: 74%
“…61 The QT interval dispersion, (difference between the longest and shortest QT intervals) a marker of vulnerability to ventricular arrhythmias and risk for sudden cardiac death, 62 is increased in OSA patients. 63 During sleep apneic episodes, cardiac arrhythmias are fairly common but in most cases benign, especially if the cardiac substrate is normal. Bradycardia prevalence and severity appears to correlate with worsening OSA severity.…”
Section: Sleep Apnea and Arrhythmiasmentioning
confidence: 99%